(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The methodology of teaching translation and translation studies plays a crucial role in the development of competent translators and researchers in the field. This article explores various approaches and strategies used in teaching translation, highlighting their effectiveness in enhancing students’ understanding and proficiency in translation. It also discusses the importance of incorporating practical translation tasks, theoretical concepts, and technological tools in the teaching process. Additionally, the article emphasizes the need for continuous professional development for translation instructors to keep pace with the evolving nature of translation studies.